THE BALANCE OF LOCAL BUDGETS IN SUBSIDIZED REGIONS - Nakhapu Ibragimova (Вестник Северо-Кавказского федерального университета)
The article deals with policy in the sphere of intergovernmental relations in the Chechen Republic, aimed at balancing the local budgets, which are the most subsidized in Russia. Analyzed the actual execution of the budget in the Chechen Republic for a certain period. Given recommendations for improving the quality of budget management at the municipal level.